The lexicon of the “act of accepting (pratigraha)”: an approach to the multilayered Vedic culture - Candotti, Maria Piera; Pontillo, Tiziana (Lingua Posnaniensis, 2019)
This joint work has its ground (and scope) in a variation-oriented reading of the Vedic sources, here applied to those which mention the act of the so-called “[gift-]acceptance” (pratigraha) within mechanisms for attaining and distributing the “goods of life” among all the members of a community. The most ancient occurrences are read and contrasted against the subsequent socio-ritual context where the well-known homonymous privilege and peculiar means of livelihood for Brahmans is depicted. The tentative interpretation of the relevant passages and the consequent reconstruction. The tentative interpretation of the relevant passages and the consequent reconstruction of the several layers of the Vedic lexicon revolving around the verbal base prati-grah- might contribute to better assessing the presence of a specific Indo-Aryan cultural matrix that might have pre-existed (and co-existed with) the mainstream Vedic world, and to better understanding how later knowledge systems succeeded in creating a new all-encompassing balance.